Phenotypical characterization of human rhinovirus infections in severely premature children (2018)
Background Human Rhinovirus (HRV) has been identified as the most common cause of acute respiratory infections and hospitalizations in premature children. It is unclear if premature children are more susceptible to HRV due to their decreased pulmonary reserve or because they have enhanced lower airway reactivity to HRV. Methods We conducted a retrospective analysis of the clinical respiratory presentation of all PCR-confirmed HRV infections in full-term and premature children aged ≤3 years in our institution. Standardized respiratory distress scores were developed to examine lower airway obstruction (i.e., wheezing, hyperinflation, and sub-costal retractions) along with markers of decreased pulmonary reserve (hypoxemia and tachypnea) in young children with HRV infections. Demographic and clinical variables were obtained from reviewing electronic medical records (EMR). Results This study included a total of 205 children; 71% of these children were born full-term (>37 weeks gestation), 10% preterm (32–37 weeks) and 19% severely premature (<32 weeks). Our results demonstrated that: 1) HRV infections in the first 3 years of life were associated with higher overall respiratory distress scores in severely premature children relative to children born preterm or full-term; 2) HRV-infected severely premature children ≤3 years old were more likely to have lower airway obstruction than HRV-infected children born preterm or full-term; and 3) other clinical signs of respiratory distress such as tachypnea and hypoxemia were not more common in severely premature than in preterm and full-term children during an HRV infection. Conclusions Our results indicate that HRV infections in severely premature children are associated with lower airway obstruction rather than hypoxemia or tachypnea. The latter suggests that enhanced airway reactivity is the underlying mechanism for the increased susceptibility to HRV in severely premature children. Longitudinal studies are needed to understand why premature babies develop airway hyper-reactivity to HRV and the long-term effects of early HRV infection in this population.